PERUBAHAN PENYAJIAN TALEMPONG GANDANG LASUANG DI NAGARI SIKAPAK TIMUR KOTA PARIAMAN - Tri Ananda; Marzam Marzam; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2018)
Abstract Talempong Gandang Lasuang is a traditional art in Nagari Sikapak Timur, Kota Pariaman. It is used as an entertainment in cooking activities in the kitchen to prepare for the Baralek (wedding ceremony). Nowadays, Talempong Gandang Lasuang art is no longer played in the kitchen, but it has become an art performance. In line, there are several changes in the presentation of Talempong Gandang Lasuang. These changes are seen from several aspects, including changes in the place of performance, instrument changes, and changes in musical form. This article was prepared based on the Thesis titled "Descriptive Study of the Performances of Talempong Gandang Lasuang in Nagari Sikapak Timur Kota Pariaman". The study was carried out using qualitative methods. Data was collected through literature study, observation, interviews and recording. Talempong Gandang Lasuang art experience changes in the place of performance which was originally performed in the kitchen.  Now, it has been performed on the show stage. Besides that, there was also an additional in the number of instruments consisting of Gandang Tambua and Talempong Gandang Lasuang. The addition of these instruments does not affect the musical form of both the melody and rhythm in Talempong Gandang Lasuang art songs. Keywords: Talempong Gandang Lasuang, Performance, Change.